Carbon balance of Hungarian grasslands in years with contrasting weather conditions - Nagy, Zoltán (Acta Biologica Szegediensis, 2005)
Net ecosystem exchange (NEE) was continuously measured by the eddy covariance technique over sandy and mountain (heavy clay soil) grasslands at Bugacpuszta and Szurdokpüspöki (Mátra) in 2003 and 2004. The heat wave in 2003 caused the grasslands to become net sources of carbon dioxide. Drought affected the C-balance of mountain grassland more adversely than that by the sandy grassland. Similar differences between the grasslands in their after drought recovery capacities (in terms of NEE) have also been observed. These differences are probably related to the different water economy of the soils and to the fact that significant part of the root system is in the upper 20 cm in the case of the grasslands. While the climate conservation potential of terrestrial vegetation is doubted, existence of a positive feedback at the global scale (between temperature and source activity of vegetation) may lead to desertification through loss of soil organic C by soil respiration as a first step.